Relationship between management and soft skills in a sample of Peruvian teachers - Soria Bustamante, Rubén Ismael (2025)
With the basic objective of analyzing the relationship between managerial management and soft skills in teachers of two schools of a UGEL in Lima, the present research, with a quantitative approach, uses a non-experimental, descriptive and correlational design. The study sample was non-probabilistic and intentional and is composed of teachers from the two schools, which total 107 and who were asked to solve two instruments: the management inventory and the soft skills questionnaire. The results obtained show the presence of significant relationships (rho = 0.81 p<.001 r2 = 65.61) between the variables that are an integral part of the research. It is also observed that the dimensions of both variables are related, so it is concluded that both the general hypothesis and the specific hypotheses have been supported.